2000
DOI: 10.1074/jbc.275.13.9587
|View full text |Cite
|
Sign up to set email alerts
|

Definition of the Interaction Domain for Cytochrome con the Cytochrome bc 1 Complex

Abstract: The interaction domain for cytochrome c on the cytochrome bc 1 complex was studied using a series of Rhodobacter sphaeroides cytochrome bc 1 mutants in which acidic residues on the surface of cytochrome c 1 were substituted with neutral or basic residues. Intracomplex electron transfer was studied using a cytochrome c derivative labeled with ruthenium trisbipyri-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…With a ⌬G ϭ 0 eV and a reasonable estimate of the reorganization energy of between 0.7 eV and 1 eV, an electron transfer rate of between 8.3 ϫ 10 6 s Ϫ1 and 9.7 ϫ 10 5 s Ϫ1 is calculated. This result compares to a measured transfer rate of 6 ϫ 10 4 s Ϫ1 for bovine QCR and horse heart CYC determined by using an artificially introduced electron donor, which affects CYC binding (32). This discrepancy suggests a significantly higher transfer rate in the natural environment than has been measured with the artificial donor.…”
Section: Resultsmentioning
confidence: 74%
“…With a ⌬G ϭ 0 eV and a reasonable estimate of the reorganization energy of between 0.7 eV and 1 eV, an electron transfer rate of between 8.3 ϫ 10 6 s Ϫ1 and 9.7 ϫ 10 5 s Ϫ1 is calculated. This result compares to a measured transfer rate of 6 ϫ 10 4 s Ϫ1 for bovine QCR and horse heart CYC determined by using an artificially introduced electron donor, which affects CYC binding (32). This discrepancy suggests a significantly higher transfer rate in the natural environment than has been measured with the artificial donor.…”
Section: Resultsmentioning
confidence: 74%
“…Electrostatic forces are considered to be a dominant factor that contributes to binding of cytochrome c to cytochrome bc 1 , which is inferred from a significant salt dependence of electron transfer between these proteins (90,114,121,135,249). An importance of short-range hydrophobic interactions between surfaces of cytochrome c 1 subunit and cytochrome c was proposed on the basis of X-ray structures of cytochrome bc 1 co-crystallized with its redox partner (152,238).…”
Section: Cytochrome C Binding Sitementioning
confidence: 99%
“…Extensive chemical modifications and mutagenic studies identified crucial amino acid residues that stabilize the complex of the proteins through interactions of negatively and positively charged residues on the surfaces of cytochrome c 1 and c, respectively (30,163,241,249). The transient binding of cytochrome c to cytochrome bc 1 in solution was inferred from the analysis of electron transfer between these proteins (175) and from the measurements based on the techniques that were independent of electron transfer, such as plasmon wave-guide resonance spectroscopy (75) or EPR (206,221,224).…”
Section: Cytochrome C Binding Sitementioning
confidence: 99%
“…Very recently, the electric field generated by the reaction center in R. sphaeroides chromatophores was found to induce electron transfer from cyt b H to cyt b L with a half-time of 0.1 ms, establishing the rate constant for this important reaction (34). We have developed a ruthenium photoexcitation method to study intracomplex electron transfer of cyt c with cyt b 5 , cyt c peroxidase, cyt c oxidase, and cyt bc 1 (35)(36)(37)(38). The rate constant for intracomplex electron transfer between cyt c and cyt c 1 was determined to be 60,000 s Ϫ1 by this method (38).…”
mentioning
confidence: 99%
“…We have developed a ruthenium photoexcitation method to study intracomplex electron transfer of cyt c with cyt b 5 , cyt c peroxidase, cyt c oxidase, and cyt bc 1 (35)(36)(37)(38). The rate constant for intracomplex electron transfer between cyt c and cyt c 1 was determined to be 60,000 s Ϫ1 by this method (38). The development of a binuclear ruthenium complex to rapidly photooxidize cyt c 1 has allowed measurement of the rate constant for electron transfer from 2Fe-2S to cyt c 1 to be 80,000 s Ϫ1 in the R. sphaeroides cyt bc 1 complex (12).…”
mentioning
confidence: 99%